Diabetes distress and fear of hypoglycaemia: what are the psychological benefits of insulin pump therapy?. (13th October 2017) - Shaban, Clare; Knott, Julia; Jenkins, Emma; Weiss, Melanie; Ryder, Jacqueline; Charman, Julie; Partridge, Helen
Abstract: Living with type 1 diabetes imposes a considerable burden on the individual to continuously self‐manage their condition. As part of an ongoing audit, the psychological outcomes of insulin pump therapy were evaluated over a three‐year period. Adult patients completed self‐report questionnaires at initiation and after 12 months of pump therapy. Diabetes emotional distress was assessed using the Problem Areas in Diabetes Scale (PAID) and cognitive and behavioural aspects of fear of hypoglycaemia using the Hypoglycaemia Fear Survey (HFS‐W, HFS‐B). HbA1c and demographic data were obtained from the clinical record. Data were collected from 190 adults, age mean (SD) years 39.6(13.9), duration of diabetes 21.0(14.1). Outcomes improved significantly from baseline to 12 months for all variables (mean [SD]): HbA1c mmol/mol 73.4(14.9), 64.6(13.1), p<0.000; PAID 23.0(14.4), 16.9(13.3), p<0.000; HFS‐W 24.1(16.3), 15.0(12.9), p<0.000; HFS‐B 19.1(9.7), 13.4(8.1), p<0.000. Paired data analysis did not indicate an association between HbA1c reduction and reduced PAID and HFS scores. It was concluded pump therapy is associated with improvements in medical and psychological variables. While a reduction in both diabetes emotional distress, and worries and behaviours related to fear of hypoglycaemia appear to be unrelated to a reduction in HbA1c, the overall burden of diabetes indicated by diabetes distress and fear of hypoglycaemia is reduced significantly 12 months after initiation of insulin pump therapy. Copyright © 2017 John Wiley & Sons.